Static and dynamic scattering from block copolymeric ring molecules - Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Scattering behavior of wormlike star macromolecules - Huber, Klaus; Burchard, Walther (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Block copolymers with rigid and flexible segments - Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Remarks on A2, hydrodynamic coil expansion, and concentration dependence of the diffusion coefficient for polystyrene in toluene - Huber, Klaus; Burchard, Walther; Akcasu, A. Ziya (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Hydrodynamic and thermodynamic behavior of short-chain polystyrene in toluene and cyclohexane at 34.5.degree.C - Huber, Klaus; Bantle, Siegfried; Lutz, Pierre; Burchard, Walther (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Semidilute solutions of star branched polystyrene: a light and neutron scattering study - Huber, Klaus; Bantle, Siegfried; Burchard, Walther; Fetters, Lewis J. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Osmotic second virial coefficient and two-parameter theories - Huber, Klaus; Stockmayer, Walter H. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dynamic light scattering from regular star-branched molecules - Huber, Klaus; Burchard, Walter; Fetters, Lewis J. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Computing residue class rings and Picard groups of orders - Klüners, Jürgen; Pauli, Sebastian (Journal of Algebra)
Let K be a global field and O be an order of K. We develop algorithms for the computation of the unit group of residue class rings for ideals O in . As an application we show how to compute the unit group and the Picard group of O provided that we are able to compute the unit group and class group of the maximal order O of K.
Keywords: Algebra and Number Theory

Radiotracer measurements as a sensitive tool for the detection of metal penetration in molecular-based organic electronics - Scharnberg, M.; Hu, J.; Kanzow, J.; Rätzke, K.; Adelung, R.; Faupel, F.; Pannemann, C.; Hilleringmann, Ulrich; Meyer, S.; Pflaum, J. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Ein Trainingsverfahren zum Erlernen der vorgegeben Teilbelastung beim Gehen mit Gehstützen - Olivier, Norbert; Hölzchen, Timo; Krug, Garvin; Wünnemann, Martin; Erlmann, Andre; Krause, Daniel; Mull, Melanie; Jöllenbeck, Thomas (Zeitschrift für Orthopädie und ihre Grenzgebiete)
Keywords: Orthopedics and Sports Medicine; Surgery

Postannealing of magnetic tunnel junctions with ion-bombardment-modified exchange bias - Höink, V.; Sacher, Marc; Schmalhorst, J.; Reiss, G.; Engel, D.; Junk, D.; Ehresmann, A. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

X-ray absorption and magnetic circular dichroism studies of annealed magnetic tunnel junctions - Schmalhorst, J.; Sacher, Marc; Thomas, A.; Brückl, H.; Reiss, G.; Starke, K. (Journal of Applied Physics)
Keywords: General Physics and Astronomy

X-ray absorption and magnetic circular dichroism studies of annealed magnetic tunnel junctions - Schmalhorst, J.; Sacher, Marc; Thomas, A.; Brückl, H.; Reiss, G.; Starke, K. (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Influence of noble-gas ion irradiation on alumina barrier of magnetic tunnel junctions - Sacher, Marc; Sauerwald, J.; Schmalhorst, J.; Reiss, G. (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Robust speaker direction estimation with particle filtering - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Workshop on Multimedia Signal Processing (MMSP 2004))
The paper is concerned with binaural signal processing for a bimodal human-robot interface with hearing and vision. The two microphone signals are processed to obtain an enhanced single-channel input signal for the subsequent speech recognizer and to localize the acoustic source, an important information for establishing a natural human-robot communication. We utilize a robust adaptive algorithm for filter-and-sum beamforming (FSB) and extract speaker direction information from the resulting FIR filter coefficients. Further, particle filtering is applied which conducts a nonlinear Bayesian tracking of speaker movement. Good location accuracy can be achieved even in highly reverberant environments. The results obtained outperform the conventional generalized cross correlation (GCC) method.
Keywords: bimodal human-robot interface; binaural signal processing; enhanced single-channel input signal; filter-and-sum beamforming; filtering theory; FIR filter coefficient; generalized cross correlation method; microphones; microphone signal; nonlinear Bayesian tracking; particle filtering; robust adaptive algorithm; robust speaker direction estimation; signal processing; speech enhancement; speech recognition; speech recognizer; user interfaces

Active Damping of Drive Train Oscillations for an Electrically Driven Vehicle - Amann, Notker; Böcker, Joachim; Prenner, Franz (IEEE/ASME Transactions on Mechatronics)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Formal Refinement and Model Checking of An Echo Cancellation Unit - Krupp, Alexander; Müller, Wolfgang; Oliver, Ian (Proceedings of DATE’04 Designers' Forum)
This article presents an approach, which combines theorem proving-based refinement with model checking for state based real-time systems. Our verification flow starts from UML state diagrams, which are translated to the formal B language and are model checked for real-time properties. By means of the B language and a B theorem prover, refined state diagrams are verified against their abstract representation. The approach is presented by means of the refinement of a digital echo cancellation unit.
Keywords: Echo cancellers; Logic; Unified modeling language; Automata; Data structures; Boolean functions; Electronic design automation and methodology; Prototypes; Specification languages; Constraint theory

Preparation of Acyloins by Cerium-Catalyzed, Direct Hydroxylation of β-Dicarbonyl Compounds with Molecular Oxygen - Christoffers, Jens; Werner, Thomas; Unger, Sven; Frey, Wolfgang (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of a tin-functionalized cyclopentadiene derivative - Christoffers, Jens; Werner, Thomas; Baro, Angelika; Fischer, Peter (Journal of Organometallic Chemistry)
Keywords: Materials Chemistry; Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Confined phonons in glasses - A study by nuclear inelastic absorption and Raman scattering - Asthalter, T.; Bauer, Matthias; van Bürck, U.; Sergueev, I.; Franz, H.; Chumakov, A.I. (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Colloid–polymer mixtures in solution with refractive index matched acrylate colloids - Kramer, Thomas; Scholz, Stephanie; Maskos, Michael; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Formation of Branched Calixarene AggregatesA Time-Resolved Static Light Scattering Study - Witte, Thomas; Decker, Björn; Mattay, Jochen; Huber, Klaus (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Particle scattering factor of pearl necklace chains - Schweins, Ralf; Huber, Klaus (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

X-ray absorption and magnetic circular dichroism studies of ion-bombarded ferromagnet-antiferromagnet bilayers - Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G.; Engel, D.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

X-ray absorption and magnetic circular dichroism studies of ion-bombarded ferromagnet-antiferromagnet bilayers - Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G.; Engel, D.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Initialization of unidirectional anisotropy in a ferromagnet–antiferromagnet bilayer by keV-He ion bombardment - Engel, D.; Ehresmann, A.; Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G. (Journal of Magnetism and Magnetic Materials)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Interface structure and magnetism of magnetic tunnel junctions with aCo2MnSielectrode - Schmalhorst, J.; Kämmerer, S.; Sacher, Marc; Reiss, G.; Hütten, A.; Scholl, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Thermal annealing of junctions with amorphous and polycrystalline ferromagnetic electrodes - Dimopoulos, T.; Gieres, G.; Wecker, J.; Wiese, N.; Sacher, Marc (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Deuterium NMR Study of Slow Relaxation Dynamics in a Polymer-like Micelles System after Flow-Induced Orientation - Angelico, R.; Burgemeister, D.; Ceglie, A.; Olsson, U.; Palazzo, G.; Schmidt, Claudia (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Morphology and fluorescence quenching in photovoltaic samples containing fullerene and poly(p-phenylene-vinylene) derivatives - Röder, T; Kitzerow, Heinz-Siegfried; Hummelen, J.C (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Cerium-Catalyzed Reaction ofβ-Dicarbonyl Compounds with Styrene and Atmospheric Oxygen - Christoffers, Jens; Werner, Thomas; Frey, Wolfgang; Baro, Angelika (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Two- and three-dimensional photonic crystals made of macroporous silicon and liquid crystals - Mertens, Guido; Röder, Thorsten; Matthias, Heinrich; Marsmann, Heinrich; Kitzerow, Heinz-Siegfried; Schweizer, Stefan L.; Jamois, Cecile; Wehrspohn, Ralf B.; Neubert, Mary (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Calcium Induced Shrinking of NaPA Chains: A SANS Investigation of Single Chain Behavior - Schweins, Ralf; Lindner, Peter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dilute solution behaviour of sodium polyacrylate chains in aqueous NaCl solutions - Schweins, Ralf; Hollmann, Jutta; Huber, Klaus (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Aggregation of a Pseudoisocyanine Chloride in Aqueous NaCl Solution - Herzog, Bernd; Huber, Klaus; Stegemeyer, Horst (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Preparation of Positively and Negatively Charged Organic Colloids from a Single Precursor - Röder, Thorsten; Kramer, Thomas; Huber, Klaus; Kitzerow, Heinz-Siegfried (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Quasi-elastic scattering by semiflexible rings - Huber, Klaus; Stockmayer, Walter H.; Soda, Kunitsugu (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 3. On the structure of 12-arm star molecules - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; Fetters, Lewis J. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 2. Global dimensions of 12-arm stars - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; J.^Fetters, Lewis (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 1. Linear chains - Huber, Klaus; Burchard, Walther; Bantle, Siegfried (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

First cumulant of the dynamic structure factor for rigid rings - Huber, Klaus; Stockmayer, Walter H. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Minimal discriminants for fields with small Frobenius groups as Galois groups - Fieker, Claus; Klüners, Jürgen (Journal of Number Theory)
We apply class field theory to the computation of the minimal discriminants for certain solvable groups. In particular, we apply our techniques to small Frobenius groups and all imprimitive degree 8 groups such that the corresponding fields have only a degree 2 and no degree 4 subfield.
Keywords: Algebra and Number Theory

Nanometer scale organic thin film transistors with Pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

High dynamic control of a three-level voltage-source-converter drive for a main strip mill - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Evaluation of the viscoelastic properties of a nematic dimer by cone-and-plate rheo-nuclear magnetic resonance spectroscopy and comparison with Leslie–Ericksen theory - Lukaschek, Michail; Kothe, Gerd; Schmidt, Claudia; Gomes, Alexandre E.; Polimeno, Antonino (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Lyotropic Mesophases Next to Highly Efficient Microemulsions: A 2H NMR Study - Stubenrauch, Cosima; Frank, Christian; Strey, Reinhard; Burgemeister, Daniel; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

In Situ Deuteron NMR Investigations of Sheared Liquid Crystalline Polymers - Siebert, Hartmut; Becker, Patrick; Quijada-Garrido, Isabel; Grabowski, David A.; Schmidt, Claudia (Solid State Nuclear Magnetic Resonance)
Keywords: Instrumentation; Nuclear and High Energy Physics; General Chemistry; Radiation

Scanning near-field optical microscopy of cholesteric liquid crystals - Huser, Thomas; Lacoste, Thilo; Heinzelmann, Harry; Kitzerow, Heinz-Siegfried (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Construction of Quaternary Stereocenters by Nickel-Catalysis of Asymmetric Michael Reactions - Christoffers, Jens; Rößler, Ulrich; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Quantum Key Distribution with Bright Entangled Beams - Silberhorn, Ch.; Korolkova, N.; Leuchs, G. (Physical Review Letters)
Keywords: General Physics and Astronomy

Collapse of sodium polyacrylate chains in calcium salt solutions - Schweins, R.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

A comparative experimental study of the aggregation of Acid Red 266 in aqueous solution by use of 19F-NMR, UV/Vis spectroscopy and static light scattering - Neumann, Bernd; Huber, Klaus; Pollmann, Peter (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Ca2+ and Cu2+ Induced Conformational Changes of Sodium Polymethacrylate in Dilute Aqueous Solution - Ikeda, Yuko; Beer, Michael; Schmidt, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Model of Polydisperse Wormlike Stars and Its Application to Dyestuff Aggregates - Katzenstein, Armin; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shift of the photonic band gap in two photonic crystal/liquid crystal composites - Mertens, Guido; Röder, Thorsten; Schweins, Ralf; Huber, Klaus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Optoelectronic system integration on silicon: waveguides, photodetectors, and VLSI CMOS circuits on one chip - Hilleringmann, Ulrich; Goser, K. (IEEE Transactions on Electron Devices)
Keywords: Electrical and Electronic Engineering; Electronic; Optical and Magnetic Materials

Characterization of submicron NMOS devices due to visible light emission - Schönstein, I.; Müller, J.; Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Results of monolithic integration of optical waveguides, photodiodes and CMOS circuits on silicon - Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

System integration of optical devices and analog CMOS amplifiers - Brass, E.; Hilleringmann, Ulrich; Schumacher, K. (IEEE Journal of Solid-State Circuits)
Keywords: Electrical and Electronic Engineering

System integration of optical devices and analog CMOS amplifiers - Brass, E.; Hilleringmann, Ulrich; Schumacher, K. (IEEE Journal of Solid-State Circuits)
Keywords: Electrical and Electronic Engineering

Characterisation of sub-100 nm-MOS-transistors processed by optical lithography and a sidewall-etchback technique - Horstmann, J.T.; Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

VLSI technologies for artificial neural networks - Goser, K.; Hilleringmann, Ulrich; Rueckert, U.; Schumacher, K. (IEEE Micro)
Keywords: Electrical and Electronic Engineering; Hardware and Architecture; Software

A novel insulation technique for smart power switching devices and very high voltage ICs above 10 kV - Mankowski, V.; Hilleringmann, Ulrich; Schumacher, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

1/f-Noise of sub-100 nm-MOS-transistors fabricated by a special deposition and etchback technique - Horstmann, J.T.; Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

A silicon based technology for monolithic integration of waveguides and VLSI CMOS circuits - Hilleringmann, Ulrich; Knospe, K.; Heite, C.; Schumacher, K.; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

VLSI technologies for artificial neural networks - Goser, K.; Hilleringmann, Ulrich; Rueckert, U.; Schumacher, K. (IEEE Micro)
Keywords: Electrical and Electronic Engineering; Hardware and Architecture; Software

Floating gate structures as nonvolatile analog memory cells in 1.0μm-LOCOS-CMOS technology with PZT dielectrica - Soennecken, A.; Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Results of monolithic integration of optical waveguides, photodiodes and CMOS circuits on silicon - Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

CMOS compatible micromachining by dry silicon-etching techniques - Adams, S.; Hilleringmann, Ulrich; Goser, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Matching analysis of deposition defined 50-nm MOSFET's - Horstmann, J.T.; Hilleringmann, Ulrich; Goser, K.F. (IEEE Transactions on Electron Devices)
Keywords: Electrical and Electronic Engineering; Electronic; Optical and Magnetic Materials

12 kV low current cascaded light triggered switch on one silicon chip - Mankowski, V.; Hilleringmann, Ulrich; Schumacher, K. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Matching analysis of deposition defined 50-nm MOSFET's - Horstmann, J.T.; Hilleringmann, Ulrich; Goser, K.F. (IEEE Transactions on Electron Devices)
Keywords: Electrical and Electronic Engineering; Electronic; Optical and Magnetic Materials

Mesoscopic transport phenomena in ultrashort channel MOSFETs - Wirth, G; Hilleringmann, Ulrich; Horstmann, J.T; Goser, K (Solid-State Electronics)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Structures with a minimum feature size of less than 100 nm in CVD-diamond for sensor applications - Otterbach, R.; Hilleringmann, Ulrich; Horstmann, T.J.; Goser, K. (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

A structure definition technique for 25 nm lines of silicon and related materials - Hilleringmann, Ulrich; Vieregge, T.; Horstmann, J.T. (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Reactive ion etching of CVD-diamond for piezoresistive pressure sensors - Otterbach, R.; Hilleringmann, Ulrich (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

A finite element algorithm for parameter identification of material models for fluid saturated porous media - Mahnken, Rolf; Steinmann, P. (International Journal for Numerical and Analytical Methods in Geomechanics)
Keywords: Mechanics of Materials; Geotechnical Engineering and Engineering Geology; General Materials Science; Computational Mechanics

Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Implicit integration scheme and its consistent linearization for an elastoplastic-damage model with application to concrete - Mahnken, Rolf; Tikhomirov, D.; Stein, E. (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Improved implementation of an algorithm for non-linear isotropic/kinematic hardening in elastoplasticity - Mahnken, Rolf (Communications in Numerical Methods in Engineering)
Keywords: Applied Mathematics; Computational Theory and Mathematics; General Engineering; Modeling and Simulation; Software

Numerical simulation of interface debonding with a combined damage/friction constitutive model - Döbert, C.; Mahnken, Rolf; Stein, E. (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

A comprehensive study of a multiplicative elastoplasticity model coupled to damage including parameter identification - Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Parameter identification of gradient enhanced damage models with the finite element method - Mahnken, Rolf; Kuhl, Ellen (European Journal of Mechanics - A/Solids)
Keywords: General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter estimation for a viscoplastic damage model using a gradient‐based optimization algorithm - Mahnken, Rolf; Johansson, Magnus; Runesson, Kenneth (Engineering Computations)
In this work a gradient‐based optimization method is applied in order to determine material parameters for a viscoplastic model with dynamic yield surface coupled to damage as presented in 1997. To this end a sensitivity analysis consistent with the integration scheme presented previously is performed in a systematic manner, both for strain and stress controlled experiments. The algorithm is tested in two numerical examples: first, simulated data are used, in order to re‐obtain parameters for the case of damage under monotonic loading. In the second example material parameters are obtained based on experimental data for lcf‐testing of an austenetic stainless steel, thus showing a very good agreement with respect to hardening, rate and damage effects.
Keywords: Computational Theory and Mathematics; Computer Science Applications; General Engineering; Software

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

The identification of parameters for visco-plastic models via finite-element methods and gradient methods - Mahnken, Rolf; Stein, E (Modelling and Simulation in Materials Science and Engineering)
Keywords: Computer Science Applications; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Customer-Oriented Systems Design through Virtual Prototyps - Flake, Stephan; Geiger, Christian; Müller, Wolfgang; Ruf, Jürgen (Proceedings of IEEE KMN 2001)
Rapid prototyping based on 3D models is well accepted for several applications. This article addresses the application of animated virtual 3D prototypes for the development of computer-based systems supporting early collaboration of the system designer with the external customer. Our methodology seamlessly integrates illustration through 3D animation with the main tasks of computer-based real-time systems development, i.e., implementation and verification. The approach is outlined by the example of the design of a flexible manufacturing system.
Keywords: Virtual prototyping; Animation; Collaboration; System analysis and design; Feedback; Application software; Power system modeling; Handicapped aids; Process design; Contracts

The Simulation Semantics of SystemC - Müller, Wolfgang; Ruf, Jürgen; Hoffmann, D. W.; Gerlach, Joachim; Kropf, Thomas; Rosenstiehl, W. (Proceedings of the Design, Automation, and Test in Europe (DATE’01))
We present a rigorous but transparent semantics definition of SystemC that covers method, thread, and clocked thread behavior as well as their interaction with the simulation kernel process. The semantics includes watching statements, signal assignment, and wait statements as they are introduced in SystemC V1.O. We present our definition in form of distributed Abstract State Machines (ASMs) rules reflecting the view given in the SystemC User's Manual and the reference implementation. We mainly see our formal semantics as a concise, unambiguous, high-level specification for SystemC-based implementations and for standardization. Additionally, it can be used as a sound basis to investigate SystemC interoperability with Verilog and VHDL.
Keywords: Yarn; Formal verification; Kernel; Hardware design languages; Electronic design automation and methodology; Algebra; Computational modeling; Logic functions; Computer languages; Clocks

A Database for Field Extensions of the Rationals - Klüners, Jürgen; Malle, Gunter (LMS Journal of Computation and Mathematics)
This paper announces the creation of a database for number fields. It describes the contents and the methods of access, indicates the origin of the polynomials, and formulates the aims of this collection of fields.
Keywords: Computational Theory and Mathematics; General Mathematics

State of the art and development trends of ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics Symposium, 2000 IEEE)
Ultrasonic linear motors have now been investigated for several years. Their key features are high thrust forces related to their volume and good position-accuracy. This contribution consists of two main parts. In the first part we describe the state-of-the-art of linear piezoelectric motors. Characteristics like no-load velocity, maximum thrust force and other technical properties of commercially available devices will be reported as well as those of prototypes. In the second part we report an ongoing research and development project aiming at a linear piezoelectric motor, which is capable of surpassing some of the shortcomings of other piezoelectric motors
Keywords: linear motors; ultrasonic motors; linear piezoelectric motor; maximum thrust force; no-load velocity; ultrasonic linear motor; Electromagnetic devices; Electromagnetic fields; Frequency; Friction; Gears; Materials science and technology; Piezoelectric materials; Research and development; Vibrations; Wheels

Flow Behavior of Two Side-Chain Liquid Crystal Polymers Studied by Transient Rheology - Quijada-Garrido, Isabel; Siebert, Hartmut; Friedrich, Christian; Schmidt, Claudia (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Asymmetric switching and storage effects in ferroelectric and antiferroelectric gels and polymers - Glossmann, Jochen; Hoischen, Andreas; Roder, Thorsten; Kitzerow, Heinz-Siegfried (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Time-Resolved Recording of Ionic Dyestuff Aggregation by Static Light Scattering - Inglés, Sergio Escudero; Katzenstein, Armin; Schlenker, Wolfgang; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science